2000
DOI: 10.1007/s003800070038
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid induces vascular smooth muscle cell death via hydroxyl radical production

Abstract: In the present study, we investigated whether gallic acid (GA) can induce death in cultured vascular smooth muscle cells (VSMCs), and whether production of the hydroxyl radical (.OH) is involved in the process of GA action. GA killed cultured VSMCs from rat aorta, in a dosc- and time-dependent manner. Cytoplasmic shrinkage and nuclear condensation were observed light microscopically in GA-treated VSMCs, which appeared apoptotic. However, the ultrastructure of the VSMC was not typical of apoptosis: nuclear cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…With regard to gallic acid (a myricetin metabolite), which displayed a strong antiproliferative effect on B16F10 and Melan-a, ours results confirm those of Ohno et al (2001) [52] and Qiu et al (2000) [53], who suggested that such effects are due to its hydroxylated aromatic structure and not to the presence of a carboxyl group, because trimethoxybenzoic acid showed no such effect on the inhibition of cell growth.…”
Section: Antiproliferative Effectssupporting
confidence: 89%
“…With regard to gallic acid (a myricetin metabolite), which displayed a strong antiproliferative effect on B16F10 and Melan-a, ours results confirm those of Ohno et al (2001) [52] and Qiu et al (2000) [53], who suggested that such effects are due to its hydroxylated aromatic structure and not to the presence of a carboxyl group, because trimethoxybenzoic acid showed no such effect on the inhibition of cell growth.…”
Section: Antiproliferative Effectssupporting
confidence: 89%
“…However, other studies have reported the cytotoxic activity of gallic acid. 37,38 Additionally, gallic acid has been reported to have both pro-oxidant and antioxidant properties. 39 …”
Section: Introductionmentioning
confidence: 99%
“…This antioxidant effect could prove beneficial to numerous disease states, including cardiovascular disease. However, other studies have highlighted the cytotoxic activity of gallic acid: (a) antitumoral effects via apoptosis in certain tumor cell lines [5,6]; (b) cytotoxicity in vascular smooth muscle cells [7] and hepatocytes [8].…”
Section: Introductionmentioning
confidence: 99%